Experiments with light and color - Jackson, Tom, 1972- (New York : Gareth Stevens Pub., 2010)
Contains step-by-step, illustrated instructions for experiments and activities involving principles pertaining to color and light, with troubleshooting and safety tips.
Two-way mirror -- Make a rainbow -- Fishbowl lens -- Disappearing trick -- Make a telescope -- Trapped beam -- Pinhole camera -- Spectrometer -- Make Moiré patterns -- Sunset in a glass -- Separating colors.
Includes bibliographical references (p. 31 ) and index.
4.8
3-6
3-6
Keywords: Colors -- Experiments -- Juvenile literature; Light -- Experiments -- Juvenile literature; Optics -- Experiments -- Juvenile literature; Color -- Experiments; Light -- Experiments; Optics -- Experiments; Color -- Experiments; Light -- Experiments; Optics -- Experiments